Hierarchical Interconnected NiMoN with Large Specific Surface Area and High Mechanical Strength for Efficient and Stable Alkaline Water/Seawater Hydrogen Evolution - Ning, Minghui; Wang, Yu; Wu, Libo; Yang, Lun; Chen, Zhaoyang; Song, Shaowei; Yao, Yan; Bao, Jiming; Chen, Shuo; Ren, Zhifeng (Nano-Micro Letters, 2023)
NiMo-based nanostructures are among the most active hydrogen evolution reaction (HER) catalysts under an alkaline environment due to their strong water dissociation ability. However, these nanostructures are vulnerable to the destructive effects of H2 production, especially at industry-standard current densities. Therefore, developing a strategy to improve their mechanical strength while maintaining or even further increasing the activity of these nanocatalysts is of great interest to both the research and industrial communities. Here, a hierarchical interconnected NiMoN (HW-NiMoN-2h) with a nanorod-nanowire morphology was synthesized based on a rational combination of hydrothermal and water bath processes. HW-NiMoN-2h is found to exhibit excellent HER activity due to the accomodation of abundant active sites on its hierarchical morphology, in which nanowires connect free-standing nanorods, concurrently strengthening its structural stability to withstand H2 production at 1 A cm−2. Seawater is an attractive feedstock for water electrolysis since H2 generation and water desalination can be addressed simultaneously in a single process. The HER performance of HW-NiMoN-2h in alkaline seawater suggests that the presence of Na+ ions interferes with the reation kinetics, thus lowering its activity slightly. However, benefiting from its hierarchical and interconnected characteristics, HW-NiMoN-2h is found to deliver outstanding HER activity of 1 A cm−2 at 130 mV overpotential and to exhibit excellent stability at 1 A cm−2 over 70 h in 1 M KOH seawater. Highlights: 1 A hierarchical interconnected NiMoN (HW-NiMoN-2h) was successfully prepared based on a rational combination of hydrothermal and water bath processes. 2 HW-NiMoN-2h exhibited high hydrogen evolution reaction (HER) activity due to its large specific surface area and good stability due to its enhanced mechanical strength. 3 In 1 M KOH seawater, HW-NiMoN-2h delivered current density of 1 A cm−2 for HER at an overpotential of 130 mV and showed excellent stability over 70 h at 1 A cm−2.